Rate of Recurrent Luminal Esophageal Cancer in Asymptomatic Patients After Curative Treatment for Esophageal Cancer. Issue 8 (September 2015) - Lin, Cui Li; Meredith, Kenneth; Klapman, Jason
Abstract : Goals: The goal of this study was to determine the luminal recurrence rate of asymptomatic patients undergoing annual surveillance esophagogastroduodenoscopy (EGD). Background: Current guidelines recommend surveillance EGD in postesophagectomy patients with esophageal cancer if there is clinical suspicion of local recurrence. However, many patients undergo annual surveillance EGD despite the recommendations to the contrary. Study: A query was performed of all patients who underwent esophagectomy between January 2000 and April 2010 at Moffitt Cancer Center. Patients were included if: they underwent esophagectomy with curative intent, had at least 12 months of follow-up after surgery, and had a R0 resection. Clinical and pathologic data in patients with and without recurrent disease were compared using the Fisher exact tests. Mean differences were examined using the Wilcoxon rank sum test. Results: 346 patients were included with a mean age of 63.5±10.4 years and mean follow-up of 40.9±24.8 months. Recurrence was detected in 89 (25.7%) patients at a mean follow-up of 17.9±15.9 months after surgery. Seventeen (19.1%) patients had recurrence involving the esophagus but 7 (7.9%) patients had associated regional or distant metastases. Nine patients had abnormal signs/symptoms prompting evaluation with EGD. One patient had isolated luminal recurrence. Conclusions: In this study the majority of patients recurred in the metastatic setting. One (0.29%) patient had localized recurrence; however, it was unclear if this patient had any symptoms or signs to prompt evaluation. Our results support the current recommendation of a symptom-base endoscopic evaluation for esophageal cancer recurrence.